Herbicides applied in pre and post-emergence to control Chamaesyce hirta - Moreli de Freitas, Naira; Inojosa Ferreira, Luiz Augusto; Francieli Vital Silva, Vanessa; Sato Teixeira, Celso Augusto; Padovese, Lucas Matheus; Silvério de Oliveira Jr, Rubem (Revista Ceres, 2022)
In view of the increase in the infested areas and the difficulty in controlling Chamaesyce hirta (L.) Millsp (garden spurge) there is growing interest in identifying herbicides that can be applied in pre and post-emergence, helping to reduce infestation and to provide species control. The objective of this work was to evaluate efficient alternatives of herbicides applied in pre and post emergence aiming at the control of Chamaesyce hirta. Three experiments were carried out in a greenhouse in a completely randomized design with four replications. The first with the application of herbicides in pre-emergence, the second with the application of herbicides in post-emergence when the plants of C. hirta had two to four true leaves fully expanded, and the third experiment, also with the post-emergence application at the flowering and branching stage of the plants. For herbicides applied in pre-emergence, at 28 days after application (DAA), all herbicides evaluated were considered effective for the control of Chamaesyce hirta, showing results above 90%. Several herbicides were efficient in controlling the species with two to four leaves, however, in the flowering stage, there is greater difficulty in control, showing the importance of the plant stage at the time of application.